NASA/DoD Conference on Evolvable Hardware, 2003. Proceedings.
DOI: 10.1109/eh.2003.1217658
|View full text |Cite
|
Sign up to set email alerts
|

Easily testable image operators: the class of circuits where evolution beats engineers

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…More recently, Garvie and Thompson [2003] have directly evolved simple digital circuits containing a built-in self-test system. Sekanina and Ruzicka [2003] demonstrated that inherently easily testable image filters can be generated automatically for real-world applications. Lohn et al [2003] performed functional recovery of a quadrature decoder after a stuck-at-zero fault for a model of an FPGA.…”
Section: Evolutionary Approaches In the Field Of Testing Of Digital Cmentioning
confidence: 99%
“…More recently, Garvie and Thompson [2003] have directly evolved simple digital circuits containing a built-in self-test system. Sekanina and Ruzicka [2003] demonstrated that inherently easily testable image filters can be generated automatically for real-world applications. Lohn et al [2003] performed functional recovery of a quadrature decoder after a stuck-at-zero fault for a model of an FPGA.…”
Section: Evolutionary Approaches In the Field Of Testing Of Digital Cmentioning
confidence: 99%
“…A number of papers have dealt with the evolutionary image filter design at the hardware level (see e.g. Burian and Takala, 2004;Dumoulin et al, 2000;Erba et al, 2001;Hollingworth et al, 1999;Porter, 2001;Sekanina, 2004;Sekanina and Ruzicka, 2003;Smith et al, 2005;Zhang et al, 2004a,b). In most cases, candidate circuits were evaluated in a reconfigurable device while EA was executed on a personal computer or a cluster of workstations.…”
Section: Introductionmentioning
confidence: 99%
“…Garvie and Thompson have directly evolved simple digital circuits from the scratch containing a built-in self-test system [3]. Sekanina and Ruzicka have demonstrated that inherently easily testable image filters can be generated automatically for real-world applications [10]. Lohn et al performed functional recovery of a quadrature decoder after a stuck-at-zero fault for a model of the FPGA [8].…”
Section: Evolutionary Approaches In the Field Of Diagnostics And Testmentioning
confidence: 99%